Innovative leadership and sustainability in higher education management - Maria Flori; Elena-Cristina Raulea; Ciprian Raulea (Computers and Education Open, 2025)
This study proposes a sustainability-driven vector model designed to enhance adaptive governance and decision-making in higher education. Drawing from systems theory, sustainability science, and mathematical logic—including automorphic transformations and fractal reasoning—the model incorporates continuous feedback loops and vector-based structures to simulate institutional processes such as leadership, sensing, and strategic coordination. Unlike traditional linear management models, the proposed framework enables dynamic, data-informed responses to educational disruptions through recursive logic and commutative diagrams. A dual-scenario application demonstrates its relevance for optimizing digital infrastructure, improving resource allocation, and supporting anticipatory leadership in hybrid and technology-integrated environments. By aligning interdisciplinary theory with operational logic, this study contributes a replicable framework for advancing institutional agility, resilience, and sustainability in the context of digital transformation in higher education.